Análisis de corrosión de elementos finitos en un tornillo dental - Ulquiango Caza, Samantha Nayeli (2024)
In the titration work, a finite element analysis of a dental implant is carried out, for which its properties and behavior have been examined in detail with respect to the applied grade 5 Titanium material. In this project, a thorough analysis is involved, this involves simulation, properties and characteristics of the screw and its environment were assigned, validating the degenerative process through the use of specialized software such as Ansys. The modeling was carried out through the program called Solidworks and the choice of the material was based on the bibliographic search to determine the materials that are assigned in the specialized software. The purpose of this approach is to identify and understand the mechanical and chemical processes of biomaterials involved in the dental implant.